Scalable synthesis of manganese-doped hydrated vanadium oxide as a cathode material for aqueous zinc-metal battery - Ghosh, Meena; Dilwale, Swati; Vijayakumar, Vidyanand; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2020)
Rechargeable aqueous zinc-metal batteries (ZMBs) are considered as potential energy storage devices for stationary applications. Despite the significant developments in recent years, the performance of ZMBs is still limited due to the lack of advanced cathode materials delivering high capacity and long cycle life. In this work, we report a low-temperature and scalable synthesis method following a surfactant-assisted route for preparing manganese-doped hydrated vanadium oxide (MnHVO-30) and its application as the cathode material for ZMB. The as-prepared material possesses a porous architecture and expanded interlayer spacing. Therefore, the MnHVO-30 cathode offers fast and reversible insertion of Zn2+ ions during the charge/discharge process and delivers 341 mAh g(-1) capacity at 0.1 A g(-1). Moreover, the MnHVO-30 parallel to Zn cell retains 82% of its initial capacity over 1200 stability cycles, which is higher compared to that of the undoped system. Besides, a quasi-solid-state home-made pouch cell with an area of 3.3 x 1.6 cm(2) and 3.6 mg cm(-2) loading is assembled, achieving 115 mAh g(-1) capacity over 100 stability cycles. Therefore, this work provides an easy and attractive way for preparing efficient cathode materials for aqueous ZMBs.
Keywords: anionic surfactant; hydrated vanadium pentoxide; Nafion ionomer membrane; post-lithium battery; quasi-solid-state battery